Implementation of Deming Model-Based Performance Management on PT Berkah Travel Pamedan (Proceeding International Collaborative Conference on Multidisciplinary Science, 2024)
The purpose of this study is to describe the implementation of performance management based on the Deming model at PT Berkah Travel Pamedan. Using a descriptive method with a qualitative approach, data collection was conducted through observation and interviews. The sample was selected through purposive sampling, with key staff of PT Berkah Travel Pamedan as the primary informants. The findings reveal that the implementation of performance management based on the Deming model has been carried out effectively. At the Plan stage, employees are trained to understand their responsibilities by utilizing systems provided by the airlines to support operational activities. At the Do stage, operations rely on the integrated online systems of the airlines. At the Check stage, performance monitoring is conducted through a report system that automatically records all employee activities. Lastly, at the Act stage, the company applies corrective actions, such as issuing warnings, to address errors or declines in employee performance, ensuring continuous improvement in operational effectiveness.